PEMAKNAAN KEKERASAN BERBASIS GENDER ONLINE DALAM FILM LIKE & SHARE (ANALISIS RESEPSI AUDIENS FILM LIKE & SHARE): Bahasa Indonesia - Pawestry, Ezarine Vani Indirra (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
Online gender-based violence cases has recently increased statistically in Indonesia. The movie Like & Share by Gina S. Noer shows how online gender-based violence happens to women. This research uses descriptive qualitative methods and uses Stuart Hall's reception theory as an approach. Reception analysis itself views at the activity of viewers and readers as recipients of a message produced by the sender of the message. The purpose of this research is to describe the audiences’ reception of messages which can later be classified into three reader positions based on Stuart Hall's reception theory. This research also uses a mixed method tools to gain data by doing an indepth interview and a focus group discussion, considering to hold the privacy of some informants as they are telling a sensitive experience regarding online gender-based violence. The results of this research shows that the audiences’ which consists of four informants generates various meanings as they each come from a different background, experience, morals, and values. Out of nine scenes analysis unit studied, the audiences’ reception of online gender-based violence in the movie Like & Share is dominated by dominant-hegemonic. But there are also some informants that are in the oppositional position and negotiated position.